MicroRNA-101a Inhibits Cardiac Fibrosis Induced by Hypoxia via Targeting TGFβRI on Cardiac Fibroblasts - Xin Zhao; Kejing Wang; Yuhua Liao; Qiutang Zeng; Yushu Li; Fen Hu; Yuzhou Liu; Kai Meng; Cheng Qian; Qing Zhang; Hongquan Guan; Kaige Feng; et al. (Cellular Physiology and Biochemistry, 2015)
Background/Aims: Hypoxia is a basic pathological challenge that is associated with numerous cardiovascular disorders including aberrant cardiac remodeling. Transforming growth factor beta (TGF-β) signaling pathway plays a pivotal role in mediating cardiac fibroblast (CF) function and cardiac fibrosis. Recent data suggested that microRNA-101a (miR-101a) exerted anti-fibrotic effects in post-infarct cardiac remodeling and improved cardiac function. This study aimed to investigate the potential relationship between hypoxia, miR-101a and TGF-β signaling pathway in CFs. Methods and Results: Two weeks following coronary artery occlusion in rats, the expression levels of both TGFβ1 and TGFβRI were increased, but the expression of miR-101a was decreased at the site of the infarct and along its border. Cultured rat neonatal CFs treated with hypoxia were characterized by the up-regulation of TGFβ1 and TGFβRI and the down-regulation of miR-101a. Delivery of miR-101a mimics significantly suppressed the expression of TGFβRI and p-Smad 3, CF differentiation and collagen content of CFs. These anti-fibrotic effects were abrogated by co-transfection with AMO-miR-101a, an antisense inhibitor of miR-101a. The repression of TGFβRI, a target of miR-101a, was validated by luciferase reporter assays targeting the 3'UTR of TGFβRI. Additionally, we found that overexpression of miR-101a reversed the improved migration ability of CFs and further reduced CF proliferation caused by hypoxia. Conclusion: Our study illustrates that miR-101a exerts anti-fibrotic effects by targeting TGFβRI, suggesting that miR-101a plays a multi-faceted role in modulating TGF-β signaling pathway and cardiac fibrosis.